ILLUSTRATED STORYBOOK TO IMPROVE TEENAGERS’ UNDERSTANDING OF FUTURE CAREER ASPIRATIONS: A SYSTEMATIC REVIEW - Salsabila, Diandra Zahra; Juhana, Agus (Universitas Negeri Semarang, 2025)
Planning a future career according to one's desires and skills is a hope for many people. This study was conducted to systematically review what influences adolescents in planning their future careers and whether illustration-based books can be a medium that can help them in achieving success in future career planning. The method used was a Systematic Literature Review (SLR) with reference to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines with data sources originating from international publishers and resulting in 51 articles that meet the inclusion and exclusion criteria. The results of the review found that future career planning is influenced by various factors both internally and externally, both of which have the same line in influencing motivation and emotions in individuals. Technology-based counseling guidance is needed, and interactive digital books can be a medium in conveying information in a fun way. Further research is recommended to focus more on emotions by designing fun interactive digital book media to increase adolescents' confidence in future careers that suit their desires.